Public perception towards conservation of heritage buildings in Berlin and Kuala Lumpur / Shahariah Norain Shaharuddin - Shahariah Norain , Shaharuddin (2020)
This study examines the local public perception towards the intention to conserve the heritage buildings and sites in the city area. The need for an effective public interest and integrated heritage conservation in the city is vital which resolve the issues on the demolition of historic buildings. The objective of this study is to investigate the perception of attitudes, subject norms and perceived behavior control of the local public that influence the behavior towards the intention to conserve the heritage building in the city area. This study also investigates the behavior of local public from the opinion of stakeholders towards conserving the heritage building sites in the city area in Berlin and Kuala Lumpur. The study has adopted the Theory of Reasoned Action and Theory Perceived Behavior Control to identify the interest of individuals to perform a specific behavior intention. The research design is an explanatory sequential mixed method which involves the quantitative and qualitative method by using questionnaire survey and interview. The findings from the quantitative method using PLS-SEM Path Model analysis revealed that the relationship on attitude of local public in Kuala Lumpur was supported the intention, however, in Berlin, the relationship was not supported the intention to conserve the heritage buildings in the city area. Perhaps, every area or whether in Asia and Europe has a distinctive cultural style for each urban and city area. Also, the elimination of data during validity and reliability cause the means of the results were imbalance for data in Kuala Lumpur. Meanwhile, the findings for subjective norms and perceived behavior control have supported the intention to conserve the heritage buildings for both countries in KL and Berlin. The qualitative results indicated that public perception of behavior from stakeholders’ opinion that the local public aware the importance to conserve the heritage building because it represents brand and product as city identity, the sense of place to individual, community and society, the education and knowledge is important to increase awareness and due to lack of motivation and support has made the public involvement less interest. The heritage buildings and sites are essential to city development because heritage is the reflection of community and society history; it will able to understand and respect people who lived before for the benefits to generation.